EVALUASI KINERJA TATA LETAK RUANG PUBLIK DITINJAU DARI PERSEPSI DAN PERILAKU PENGGUNA (STUDI KASUS RUANG TERBUKA TEPI PANTAI ULEE LHEUE) - Rikza, Rikza; Zulfadhli (Jurnal Media Teknik Sipil Samudra, 2025)
Coastal public spaces play a strategic role in supporting social interaction, recreational activities, and urban environmental quality. However, the quality of public space is not solely determined by physical aspects, but also by the compatibility of spatial layout with users’ perceptions and behaviors. This study aims to evaluate the performance of public building spatial layout in the coastal open space of Ulee Lheue Beach, Banda Aceh City, based on users’ perceptions and behaviors. The research employed a qualitative evaluative approach through behavioral observation, in-depth interviews, and documentation. The findings indicate that Ulee Lheue Beach has strong visual and physical potential as a coastal public space, particularly in terms of openness and natural scenery. Nevertheless, the spatial layout has not fully responded to users’ activity patterns and needs, as reflected by limited spatial connectivity, unclear zoning, and the emergence of adaptive user behaviors in utilizing space informally. The study concludes that the performance of the public space layout at Ulee Lheue Beach remains suboptimal and requires reconfiguration that prioritizes user experience, perception, and behavior to create a functional, inclusive, and sustainable coastal public space.